Lime-enhanced carbon monoxide reduction of cuprous sulfide - Mohan M.K.; Mankhand T.R.; Prasad P.M. (My University, 2025)
Kinetic studies were conducted on the carbon monoxide reduction of cuprous sulfide powder in the presence of lime as a function of quantity of lime in the charge, CO flowrate, temperature, and time of reduction and particle size of the sulfide. Lime was found to enhance drastically the rate of reduction as well as reduce the COS emission into the off-gas to negligible levels. Both temperature and flowrate of the reducing gas were found to influence the reduction rate, and best results were obtained at 1273 K and at a CO flowrate of 3.33 cm3 s-1. The overall reaction seems to be governed by the intrinsic kinetics of the Cu2S-CO reaction. Kinetic analysis reveals the observance of the Valensi's equation, indicating diffusional control through the product layer formed over reacting Cu2S particles. The calculated experimental activation energy of 169.6 kJ/mole in the termperature range of 1123 to 1273 K is in good agreement with that reported in the literature for sulfur diffusion in copper. A critical comparison has been made of the lime-scavenged reduction of Cu2S by different reagents, namely, hydrogen, carbon monoxide, and carbon. © 1987 The Metallurgical Society and ASM International.